Effect of heat treatment on the physical and structural properties of tellurite glass - Syarifah Fazilah Yuhari; Asmahani Awang; Mohd Azrul Abdul Rajak; Jedol Dayou (Faculty of Science and Natural Resources, 2021)
This study reports the spectroscopic properties of tellurite glass with a composition of 70TeO2-20ZnO-9.5Na2O-0.5Er2O3 synthesized using the melt-quenching technique. The physical and structural properties of glass heat treated at distinctive temperatures are found to vary due to the structural changes. The incorporation of erbium content into tellurite glass causes the glass to appear reddish in color and transparent. However, glass heat-treated at 400°C shows the tendency to become opaque due heat treatment near the crystallization temperature. XRD pattern indicated the amorphous nature of glass with the presence of a broad hump in the range 25° to 40°.